2013
DOI: 10.1530/rep-13-0107
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of miRNAs in equine follicle development

Abstract: Previous evidence from in vitro studies suggests specific roles for a subset of miRNAs, including miR-21, miR-23a, miR-145, miR-503, miR-224, miR-383, miR-378, miR-132, and miR-212, in regulating ovarian follicle development. The objective of this study was to determine changes in the levels of these miRNAs in relation to follicle selection, maturation, and ovulation in the monovular equine ovary. In Experiment 1, follicular fluid was aspirated during ovulatory cycles from the dominant (DO) and largest subord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 46 publications
3
39
1
2
Order By: Relevance
“…In vitro miR-378 overexpression and knockdown experiments revealed that aromatase expression, and therefore, estradiol production, by granulosa cells is posttranscriptionally downregulated by miR-378. These findings were supported by a recent in vivo study showing that miR-378 expression in granulosa cells is dependent on the stage of follicular development and is inversely correlated to the levels of estradiol in the follicular fluid (41). The expression of microRNAs in ovarian cumulus cells has been reported recently (1,35); however, the specific roles in this cell type have only begun to be explored.…”
mentioning
confidence: 65%
“…In vitro miR-378 overexpression and knockdown experiments revealed that aromatase expression, and therefore, estradiol production, by granulosa cells is posttranscriptionally downregulated by miR-378. These findings were supported by a recent in vivo study showing that miR-378 expression in granulosa cells is dependent on the stage of follicular development and is inversely correlated to the levels of estradiol in the follicular fluid (41). The expression of microRNAs in ovarian cumulus cells has been reported recently (1,35); however, the specific roles in this cell type have only begun to be explored.…”
mentioning
confidence: 65%
“…Five of the 9 miRNAs confirmed to be upregulated in atretic follicles in the present study (miR-21-5p, miR-21-3p, miR-222, miR-155, and miR-199a-5p) were also found to be increased in subordinate relative to dominant follicles on day 3 of the bovine estrous cycle using deep-sequencing rather than microarray [12]. Another miRNA, miR-378, was previously shown, together with miR-21-5p, to increase in expression in subordinate and anovulatory follicles in horses [13], [14]. Taken together, these results are consistent with an involvement of these miRNAs in follicular atresia in the monovular ovary.…”
Section: Discussionmentioning
confidence: 86%
“…Among these, miR-142, miR-21, miR-150, miR-21, miR-409a and miR-378 were abundantly expressed in large atretic follicles. Furthermore, miR-378, miR-409a and miR-21 are commonly studied [14,43,44,55,56]; for instance, the role of miR-21 is well characterized in bovines [14] and mice [57] as survival molecules of GCs. Among miRNA families, the profile of the let-7 (lethal-7) miRNA family has been explored across different stages of follicular atresia and it was observed that the expression levels of all let-7 family members were found to be downregulated in healthy and early atretic follicles, while let-7g was highly upregulated in progressively atretic follicles [54].…”
Section: Profiling Of Mirnas During Follicular Atresiamentioning
confidence: 99%
“…Several earlier studies have verified that GC apoptosis plays a pivotal role in follicular atresia and a complex array of molecular mechanisms and regulatory networks are involved in the modulation of GC apoptosis caused by extrinsic and intrinsic factors [7,31,32,33,34,35,36,37,38,39,40]. To date, microarray profiling studies of miRNAs in ovarian tissues and cells have identified large numbers of differentially expressed miRNAs during various follicular developmental processes such as primordial development [18], steroidogenesis [41,42,43], luteal development [16,44], and atresia [45,46,47]. In subsequent target prediction and functional enrichment analysis undertaken to understand their functional involvement, some miRNAs have been categorized in apoptotic pathways.…”
Section: Introductionmentioning
confidence: 99%